Landasan Teologis Pendidikan Sains Di Pondok Pesantren - Omang Komarudin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2022)
Islamic boarding schools are the oldest educational institutions in Indonesia. It has its own uniqueness in its education system. Times began to change and the education system in Islamic boarding schools had to adapt, including adjustments to the existence of science. This research will focus on the theological view of Islamic boarding school education on the existence of science. The problem is that a large number of students in Islamic boarding schools do not have a great interest in science. In addition, this research will use library research method using theological and anthropological approaches. Thus, this study shows that education in Islamic boarding schools does not have a problem with the existence of science because it is considered final. The cause of the lack of interest in students to study science is more due to the culture and environment in which the students study.